Effect of Li2O concentration on hot corrosion behaviour of Ni-based alloys in a lithium molten salt for electroreduction process. (15th April 2022) - Choi, Woo-Seok; Kim, Wan-Bae; Lim, Kyu-Seok; Cho, Soo-Haeng; Lee, Jong-Hyeon
Abstract: Spent nuclear fuel is electro-reduced in a chemically aggressive atmosphere wherein oxygen is generated at the anode in the presence of lithium molten salt containing a strong basic oxide, Li2 O. Herein, the effect of the Li2 O concentration on the hot corrosion behaviour of Haynes 263 and Inconel X-750 was investigated by immersion in molten LiCl–Li2 O salt (1, 3, and 5 wt% Li2 O) for 72–288 h at 650 ℃ under oxidizing atmosphere. For Li2 O concentrations of approximately 3%, the weight loss and the products formed by the basic fluxing mechanism differed due to the dependence on the O 2− concentration. Highlights: Effect of Li2O concentration on corrosion of Ni-based alloys was investigated. Corrosion occurred by basic fluxing with O2 − ; products varied with ≥ 3 wt% Li2O. Dense and continuous Cr-rich oxide layer prevented the inward diffusion of oxygen. Ni-rich layer hindered outward diffusion of the alloying elements in the base metal. Excess Fe appeared to be deleterious to the overall corrosion resistance.